Short-term labour transitions and informality during the COVID-19 pandemic in Latin America - Roxana Maurizio; Ana Paula Monsalvo; María Sol Catania; Silvana Martinez (Journal for Labour Market Research, 2023)
Latin America was one of the regions hardest hit by the COVID-19 pandemic. This paper analyses, from a dynamic and comparative perspective, labour transitions triggered by the pandemic in six Latin American countries: Argentina, Brazil, Costa Rica, Mexico, Paraguay, and Peru. Special attention is paid to transits around labour informality during this period. Unlike previous crises, the fall in informal occupations deepened the overall contraction in employment. This was explained by a significant increase in exit rates from these jobs and, to a lesser extent, by reductions in entry rates. Most of the informal workers who lost their jobs left the labour force. Contrary to this labour movement, transits from informal to formal jobs significantly dropped during the most critical phase in this crisis. Partial recovery in employment since mid-2020 has been led by an increase in informal jobs. The labour dynamic has been different between men and women. This study reveals the relevance of dynamic analysis to clearly identify labour transitions that occurred during a labour crisis of unprecedented intensity and characteristics in Latin America.
Keywords: J01; J08; N36; 330; COVID-19; Latin America; Labour transitions; Informality